Factors affecting greenhouse microclimate and its regulating techniques: a review - Li, G.; Tang, L.; Zhang, X.; Dong, J.; Xiao, M. (2018)
This paper reviews factors affecting greenhouse microclimate and its regulating techniques towards upgrading the greenhouse applications in the area of southeast China which have little or very basic technology integration. The microclimate of greenhouse is apparently influenced by the shape and its orientation, the wind direction, the property of covering material, and the use of insect-proof screen as they eventually affect the total solar radiation, the thermal characterises, and the flow pattern inside. The natural ventilation and sun block are the most common method to cool the greenhouse, but more efficient evaporative cooling such as pad-fan system, misting/fogging system and roof sprinkler are required with extreme temperatures. The earth to air heat exchanger and the heat storage using phase change material may be used for heating or cooling throughout the year which are more economic and energy-saving than other traditional thermal technologies. The reviewed knowledge provides insights into upgrading greenhouse applications in Ningbo area towards more sustainable and efficient greenhouse farming.